Răspuns :
x+y=11
x^2+y^2=65
S= x+y
P= x*y
(x+y)^2= x^2+ y^2+ 2xy => x^2+y^2=(x+y)^2-2xy, atunci: x^2+y^2=s^2-2p
x^2+y^2=s^2-2p => 65=11^2-2p => p=28 => x*y=28
x+y=11 => x=11-y
x*y=28
y(11-y)=28 => -y^2+11y-28=0 <=> -(y-4)(y-7)=0 => y1=4; y2=7
Daca y=4 => x=11-4 => x=7
Daca y=7 => x=11-7 => x=4
S: { (4,7); (7,4) }
x^2+y^2=65
S= x+y
P= x*y
(x+y)^2= x^2+ y^2+ 2xy => x^2+y^2=(x+y)^2-2xy, atunci: x^2+y^2=s^2-2p
x^2+y^2=s^2-2p => 65=11^2-2p => p=28 => x*y=28
x+y=11 => x=11-y
x*y=28
y(11-y)=28 => -y^2+11y-28=0 <=> -(y-4)(y-7)=0 => y1=4; y2=7
Daca y=4 => x=11-4 => x=7
Daca y=7 => x=11-7 => x=4
S: { (4,7); (7,4) }